The effects of polymorphisms in 7 candidate genes on resistance to Salmonella Enteritidis in native chickens - Tohidi, Reza; Idris, Ismail; Panandam, Jothi Malar; Bejo, Mohd Hair (Oxford University Press, 2013)
Salmonella enterica serovar Enteritidis infection is a common concern in poultry production for its negative effects on growth as well as food safety for humans. Identification of molecular markers that are linked to resistance to Salmonella Enteritidis may lead to appropriate solutions to control Salmonella infection in chickens. This study investigated the association of candidate genes with resistance to Salmonella Enteritidis in young chickens. Two native breeds of Malaysian chickens, namely, Village Chickens and Red Junglefowl, were evaluated for bacterial colonization after Salmonella Enteritidis inoculation. Seven candidate genes were selected on the basis of their physiological role in immune response, as determined by prior studies in other genetic lines: natural resistance-associated protein 1 (NRAMP1), transforming growth factor β3 (TGFβ3), transforming growth factor β4 (TGFβ4), inhibitor of apoptosis protein 1 (IAP1), caspase 1 (CASP1), lipopolysaccharide-induced tumor necrosis factor (TNF) α factor (LITAF), and TNF-related apoptosis-inducing ligand (TRAIL). Polymerase chain reaction-RFLP was used to identify polymorphisms in the candidate genes; all genes exhibited polymorphisms in at least one breed. The NRAMP1-SacI polymorphism correlated with the differences in Salmonella Enteritidis load in the cecum (P = 0.002) and spleen (P = 0.01) of Village Chickens. Polymorphisms in the restriction sites of TGFβ3-BsrI, TGFβ4-MboII, and TRAIL-StyI were associated with Salmonella Enteritidis burden in the cecum, spleen, and liver of Village Chickens and Red Junglefowl (P < 0.05). These results indicate that the NRAMP1, TGFβ3, TGFβ4, and TRAIL genes are potential candidates for use in selection programs for increasing genetic resistance against Salmonella Enteritidis in native Malaysian chickens.